Perancangan Ide Bisnis Giftery Hampers - Jessica Patrice; Marina Wardaya (Jurnal Vicidi, 2018)
This research takes the theme of designing business ideas for Giftery Hampers. This research was conducted with the aim to know the opportunities and visibility of business hampers. This study is also used to obtain data from the public on their views on business hampers and see how business opportunities from the findings of this study. The research was conducted by qualitative, quantitative, observation and literature study. In this study, the authors look for excisting problems from excisting hampers business, explore the advantages, the shortcomings of the hampers business that has been running to create a new innovation that can be given to develop business hampers. The study was conducted by interviewing competent expert in business especially hampers business to create a new innovation that can be applied in order to develop Giftery Hampers. The result of this research is the innovation that can be executed by Giftery Hampers that can give more value to Giftery Hampers brand.